Kontribusi Kesiapan Guru dan Aktivitas Belajar Siswa Terhadap Hasil Belajar pada Pembelajaran Daring Jurusan Otomotif - Hendra Suheri; Waskito Waskito (Universitas Pendidikan Ganesha, 2021)
There are still many teachers who have not been consistent in implementing virtual classroom online learning. This study aims to analyze the contribution of teacher readiness and student learning activities in using virtual classes to student learning outcomes in the automotive department at SMKN. This research is quantitative research with the type of correlational research. The research sample consisted of 52 teachers and 52 students who were obtained based on a proportional random sampling technique. The data obtained through the questionnaire instrument was tested for requirements analysis and then analyzed using descriptive techniques, correlation techniques, simple linear regression, and multiple regression. The results of data analysis show that: (1) teacher readiness contributes to learning outcomes by 18,2%; (2) the contribution of student learning activities to learning outcomes is 27,1%; and (3) the contribution of teacher readiness and student learning activities to learning outcomes together is 37,4%. Based on the results of the study, it can be concluded that teacher readiness and student learning activities have a significant positive contribution and have an important role in the learning outcomes of students in the automotive department in the use of virtual classroom media in online learning.